2014
DOI: 10.12691/education-2-12-12
|View full text |Cite
|
Sign up to set email alerts
|

Transformative Learning in the Discipline of Nursing

Abstract: Transformative education in nursing is a manifestation of the complementarity of nursing and the ecology of education with an aim to base learning and learning outcomes -knowledge, skills and competences in the ecological paradigm. The author of the research has approbated the principles of the ecology of education in the curricula and study courses of several medical colleges, as well as in the curricula of informal education. A student survey was performed to clarify how participants of different nursing stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Many of the students also expressed a change in their expectation of healthcare roles. This finding is consistent with results of similar studies among health workers that have shown different degrees of transformation among health workers with appropriate learning/teaching methods (Altobelli, 2017;Renigere, 2014). It is however important to note that true transformation takes place only when learners are able to actively take steps that acknowledge their new belief (Mezirow, 1997).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Many of the students also expressed a change in their expectation of healthcare roles. This finding is consistent with results of similar studies among health workers that have shown different degrees of transformation among health workers with appropriate learning/teaching methods (Altobelli, 2017;Renigere, 2014). It is however important to note that true transformation takes place only when learners are able to actively take steps that acknowledge their new belief (Mezirow, 1997).…”
Section: Discussionsupporting
confidence: 88%
“…Hence there is also a need for the training programme of health workers to give them adequate opportunity to reflect on their previous knowledge, values and practices with a view of transforming them positively. Such transformative learning according to Renigere (2014) will stimulate trainee health workers to learn to think independently in order to dispose of the knowledge that has at times been acquired as a result of life experience without ever thinking or asking questions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, although the ECHO model was built on the theoretical foundations of social learning theories, the findings of this study seem to resonate with transformational learning theory ( Mezirow, 2000 ). Transformative learning is a process that facilitates the transition from a transmissive pedagogical standpoint to a transformative paradigm of learning and interdependence between continuing education and practice ( Pepin et al., 2017 ; Renigere, 2014 ). It advocates for democratic education for sustainable development, whereby learners are co-creators of their own learning through questioning, critical reflection, and creativity, in order to arrive at viewpoint changes that guide their actions ( Mezirow, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reflective thinking, through self-reflection or discourse with others, allows learners to gain diverse perspectives [ 3 ] and supports transformative learning [ 4 ]. This type of learning occurs when a learner is presented with information or experiences that challenge and alters their attitudes, values, and behaviors [ 5 ]. In health sciences, transformative learning helps stimulate learners’ ability to think independently, deconstruct their preconceived ideas and what they view as logical before they adhere to it as healthcare practitioners.…”
Section: Introductionmentioning
confidence: 99%